2021
DOI: 10.1177/17588359211022886
|View full text |Cite
|
Sign up to set email alerts
|

The value of circulating fibrinogen-to-pre-albumin ratio in predicting survival and benefit from chemotherapy in colorectal cancer

Abstract: Background: To evaluate the prognostic role of circulating fibrinogen-to-pre-albumin (FPR) in colorectal cancer (CRC) with different tumor locations, and its involvement in chemosensitivity and chemoresistance. Patients and methods: A total of 2917 eligible CRC patients from multiple centers were enrolled in this prospective study, and 3 years follow-up was carried out to obtain the outcome of these patients. Circulating fibrinogen (Fib), pre-albumin (pAlb), carcinoembryonic antigen (CEA), and carbohydrate ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…The prognostic cut-off values of FPR within stage I and II CRC were 14.0 and 16.5, respectively, as reported in our previous study [ 16 ]. Binary and continuous variables were summarized as numbers and frequencies and medians and quartiles, respectively.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The prognostic cut-off values of FPR within stage I and II CRC were 14.0 and 16.5, respectively, as reported in our previous study [ 16 ]. Binary and continuous variables were summarized as numbers and frequencies and medians and quartiles, respectively.…”
Section: Methodssupporting
confidence: 75%
“…Our previous studies showed that high-grade chronic inflammation could attenuate chemosensitivity or even chemoresistance. Patients with low-grade FPR (≤ 15) showed complete response to CT; however, median-grade FPR (20 ≥ FPR > 15) and high-grade FPR (> 20) implied chemosensitivity and chemoresistance in CRC patients [ 16 ]. This study found that CT-treated FPR > 20 patients harbored the highest recurrence and death rates.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many prognostic biomarkers are used to evaluate a variety of malignant tumors, such as AFR, fibrinogen-to-prealbumin (FPR), neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio. [23][24][25][26] However, the diagnostic value of these markers for Hp-NGC remains unclear. Therefore, this study explored the clinical value of PFR and AFR in the diagnosis of Hp-NGC.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this concept, inflammation‐based indices are significantly associated with the prognosis of patients with CRC. Such indices include the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR), albumin (ALB) to fibrinogen ratio, fibrinogen to prealbumin ratio, modified Glasgow Prognostic Score (mGPS), and C‐reactive protein (CRP) to ALB ratio (CAR) 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…Such indices include the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR), albumin (ALB) to fibrinogen ratio, fibrinogen to prealbumin ratio, modified Glasgow Prognostic Score (mGPS), and C-reactive protein (CRP) to ALB ratio (CAR). [6][7][8] Moreover, malnutrition is common in patients with CRC and is associated with intolerance to anticancer treatment and poor prognosis. 9 Cumulative evidence shows that nutritional support can improve the quality of life and survival rate of patients with CRC.…”
mentioning
confidence: 99%